If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 20)(x + -6)(13x + 7) = 0 Reorder the terms: (20 + x)(x + -6)(13x + 7) = 0 Reorder the terms: (20 + x)(-6 + x)(13x + 7) = 0 Reorder the terms: (20 + x)(-6 + x)(7 + 13x) = 0 Multiply (20 + x) * (-6 + x) (20(-6 + x) + x(-6 + x))(7 + 13x) = 0 ((-6 * 20 + x * 20) + x(-6 + x))(7 + 13x) = 0 ((-120 + 20x) + x(-6 + x))(7 + 13x) = 0 (-120 + 20x + (-6 * x + x * x))(7 + 13x) = 0 (-120 + 20x + (-6x + x2))(7 + 13x) = 0 Combine like terms: 20x + -6x = 14x (-120 + 14x + x2)(7 + 13x) = 0 Multiply (-120 + 14x + x2) * (7 + 13x) (-120(7 + 13x) + 14x * (7 + 13x) + x2(7 + 13x)) = 0 ((7 * -120 + 13x * -120) + 14x * (7 + 13x) + x2(7 + 13x)) = 0 ((-840 + -1560x) + 14x * (7 + 13x) + x2(7 + 13x)) = 0 (-840 + -1560x + (7 * 14x + 13x * 14x) + x2(7 + 13x)) = 0 (-840 + -1560x + (98x + 182x2) + x2(7 + 13x)) = 0 (-840 + -1560x + 98x + 182x2 + (7 * x2 + 13x * x2)) = 0 (-840 + -1560x + 98x + 182x2 + (7x2 + 13x3)) = 0 Combine like terms: -1560x + 98x = -1462x (-840 + -1462x + 182x2 + 7x2 + 13x3) = 0 Combine like terms: 182x2 + 7x2 = 189x2 (-840 + -1462x + 189x2 + 13x3) = 0 Solving -840 + -1462x + 189x2 + 13x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 2/3=8W | | -4.2x+3.5y+2.6-5.9x-2.4y= | | 10+5z(z-2)=-2z+2 | | 2w=4/3 | | x^2-4=8x | | 5k+20-3-3k=7k | | -5/(-2)=x | | .8(x+20)+.2x=41 | | 178.7-176.9= | | 2(x+2)-9=3x-19 | | 15x+y+.25z=100 | | 2*3+4-36= | | 10x+18y=700 | | (1/3)9.9.9 | | 4(x+1)+(2x-7)=50 | | f(x)=x*x-6 | | 4/x=12-2x | | 8-9(5+7)= | | .5x+10=9 | | 7x-(6x+6)=2x-38 | | -11=0-5/6 | | 45x+26x+110=0 | | y=5x-21 | | W^2=w+1 | | 5-3(4+6)= | | 4x-2=5(x+10) | | 2-0x=-8 | | 9-2(x+3)+6x= | | e^5x+6=.46 | | 5x+12+4y=32 | | 8-2x=-26 | | -15+x=-8 |